Effect of Lifestyle Modification Upon Dysmenorrhea and Pain Severity in University Students of Karachi- Prospective Study - Sehrish Rasool, Sana Tariq, Lubna Razzak, Rabiyya Shabbir, Nida Shoaib, Khadija Hamid, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate the effect of lifestyle modification upon dysmenorrhea and pain severity in university students of Karachi. Methodology: This is a prospective cohort study, the sample size was 383 participants, and data was collected from the Karachi institute of health sciences. Participants were followed after lifestyle modifications, weight reduction, stress management, physical exercise, and nutrition. Menstruation pain severity was measured by pain visual analog scale score (VAS) score, after 4 weeks and 8 weeks of modification follow-up, participants were asked to fill a validated questionnaire including pain VAS score again to assess the difference in dysmenorrhea and its associated symptoms. Results: Out of 383 study participants, the mean age was 22.2±1.9 years while the mean weight was 72.9±4.7 years, mean age of menarche was 13.4±0.7 years. Pain VAS score was categorized within mild and tolerable, moderate and Uncomfortable, and severe with an immediate need for medical intervention, indicating 82(21.4%), 195(50.9%) and 106(27.6%) frequencies respectively. The effect of lifestyle modification afterthe first menstruation cycle questionnaire was filled again, and results indicated mild, moderate, and severe results as 277(72.3%), 90(23.4%) and 16(4.1%) while on the second cycle 343(89.5%), 34(8.8%) and 6(1.5%) were identified respectively. Conclusion: Lifestyle modification, maintaining a healthy weight, having proper nutrition, and managing stress can sufficiently reduce the chances of dysmenorrhea and decreases the severity of menstrual pain. Keywords:Dysmenorrhea, Pain-vas score, lifestyle modification